EDUCATIONAL PROGRAMS IN ENGINEERING: A PERSPECTIVE FROM THE NEW MEXICAN SCHOOL AND GENDER EQUITY - Reyes, José Ángel García; Cruz, Luz María Hernández; González, Julio Antonio Gutiérrez; Álvarez, Diana Concepción Mex; Santiago, Heribé Felipe Uribe; Chan, José Ramón Cab (Seven Editora, 2025)
Currently, stereotypes associated with professional practice persist, particularly in engineering programs. This study employs a qualitative approach, using action research, to analyze the issues related to gender equity at the Faculty of Engineering of the Autonomous University of Campeche (UACAM). The study incorporates an analysis of the guiding principles of the New Mexican School (NEM) and the UACAM university statutes to identify, design, and implement strategies, activities, and events aimed at achieving gender equity. This is accomplished through the achievement of the objectives of the Women Engineers project, maintaining a comprehensive and holistic perspective of academic training. The results show that the actions undertaken have been supported by various stakeholders, and the specific objectives have been achieved through alignment with NEM’s priority principles. These priorities include university guidelines, infrastructure, financial support, and shared responsibility in student and faculty support initiatives for professional development.DOI: https://doi.org/10.56238/sevened2025.038-050